Comparative Study of Text Editors for Scientific Paper Writing with Mathematical Notation - Wihardjo, Edy; Fatahillah, Arif; Hussen, Saddam; Anka Monalisa, Lioni (Puslitbang Akademi Relawan TIK Indonesia, 2024)
Writing scientific papers that include complex mathematical notation requires specialized text editors. This study provides a comprehensive review of various text editors, evaluating their effectiveness for tasks involving mathematical notation. The comparison includes freeware and paid software such as OpenOffice, LibreOffice, Microsoft Word, TeXmacs, and Overleaf, examining aspects like file formats, file size, installation process, learning curve, collaboration ease, and output formats. Through a detailed analysis of existing literature, the study highlights the strengths and weaknesses of each editor, with a particular focus on LaTeX's precision and versatility. The findings suggest that LaTeX is the preferred choice for its high-quality output, while Overleaf offers significant advantages for collaborative projects. Freeware options like GNU TeXmacs and LibreOffice are also viable alternatives, each with unique benefits. The study concludes with recommendations on choosing the appropriate text editor based on specific project requirements and user preferences.